Detection of post-harvest insecticide Flash 10% EC residues in wheat seeds and soil after its degradation by the UV-C - Adeeb Al-Shafiee; Jamal H. Kadhim (Kufa Journal for Agricultural Sciences)
This study aimed to test the effect of the physical factor (UV-C) in degrading of insecticide Flash residue in wheat seeds and the soil post-harvest. As for the field experiments with regard to Flash residual in the soil, the results showed that the highest concentration of the insecticide was 3.10 ppm in the seeds  produced from plants treated with Flash only, while the lowest concentration (below the detectable level) was in the wheat seeds from plants sprayed with UV-C treated Flash. As for the residual in the soil, the highest active compound concentration was 12.50 ppm appeared in the uncultivated soil treated with Flash untreated, compared to the lowest residual concentration (0.00) ppm was in soil planted with wheat plants treated with UV-C treated Flash. Findings also showed that the best exposure period to the UV-C was 20mn